Microscopic techniques used for the identification of medicinal plants: A case study of Senna. Issue 10 (3rd July 2019) - Shaheen, Shabnum; Jaffer, Mehwish; Khalid, Sana; Khan, Muhammad Asaf; Hussain, Khadim; Butt, Muhammad Moeen; Rauf Siddiqui, Abdul; Ashfaq, Muhammad; Ahmad, Mushtaq; Zafar, Muhammad; Khan, Farah
Abstract: Background: The use of quality control tool for adulteration of Senna ( Cassia aungustifolia ) a pharmaceutically very important. They were used for multiple health disorders such as constipation, indigestion, epilepsy, asthma, piles, migraine, and heart problems. Two different species of same family or same genus used commercially in Indo‐Pak using the same medicine name Senna. One named as Senna ( C. aungustifolia ) and its adulterant named as Sickle Senna ( Cassia obtusifolia ). Methodology: These two plants were analyzed using classical microscopic techniques light microscopy and the modern chemotaxonomic traits scanning electron microscopy, fluorescence studies and phytochemical studies. Results: The C. aungustifolia L. had found to be a perennial herb with trilobed pollen, diacytic, paracytic, and anisocytic stomata having smooth walled epidermal cells, whereas the C. obtusifolia stands out as a perennial shrub with spheroidal and circular pollen and paracytic type of stomata having irregular shaped epidermal cells. The powdered drug of C. aungustifolia is dark grayish green, whereas the powdered drug of C. obtusifolia is light green in color. Investigation and other techniques used in this project provided the basis for the authentication of this species. Abstract : Microscopic identification of the adulterant plants was done that were sold in market under the same name. The light microscopy and scanning electron microscopy of the selected plant were performed as a correct identification tool.